2022
DOI: 10.3390/ani12091100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Solid-State Fermented Wheat Bran on Growth Performance, Immune Function, Intestinal Morphology and Microflora in Lipopolysaccharide-Challenged Broiler Chickens

Abstract: The study evaluated the effects of dry and wet solid-state fermented wheat bran (FWB) on growth performance, immune function, intestinal morphology and microflora in lipopolysaccharide (LPS)-challenged broiler chickens. The experiment was designed as a 2 × 3 factorial arrangement. A total of 252 one-day-old Arbor Acres male broiler chickens were randomly allocated to 1 of 6 treatments: basal diet + sterile saline (negative control, NC), basal diet + LPS (positive control, PC), 7% dry FWB + sterile saline (FWB-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…This result indicates that LPS impaired intestinal digestion and absorption, which is the leading cause of decreased body weight and average daily feed intake reported in our previous study [ 40 ]. Previous studies by Gadde et al [ 41 ] and An et al [ 42 ] reported similar findings. It shows that FA improves growth performance by maintaining the intestinal structure of LPS-challenged broilers.…”
Section: Discussionsupporting
confidence: 79%
“…This result indicates that LPS impaired intestinal digestion and absorption, which is the leading cause of decreased body weight and average daily feed intake reported in our previous study [ 40 ]. Previous studies by Gadde et al [ 41 ] and An et al [ 42 ] reported similar findings. It shows that FA improves growth performance by maintaining the intestinal structure of LPS-challenged broilers.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, the addition of 5 kg/t of FSBM also significantly upregulated the relative mRNA expression levels of IL-4. The fermentation of wheat bran by Lactobacillus plantarum and Bacillus subtilis significantly enhanced IL-4 contents in broiler serum and enhanced the anti-inflammatory capacity [47].…”
Section: Effect Of Fermented Soybean Meal On Intestinal Inflammation ...mentioning
confidence: 96%
“…It can prevent the invasion of exogenous pathogens or harmful substances, while also playing a crucial role in maintaining intestinal homeostasis and physical health ( 3 , 5 ). When the mucus layer and intercellular tight junctions in the small intestine are disrupted, endotoxin produced by the metabolism of metabolizing bacteria enters and leaves the bloodstream, causing systemic and intestinal inflammation, disrupting the intestinal barrier, increasing intestinal permeability, inhibiting the absorption and transportation of nutrients in the small intestine, and leading to various chronic diseases ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%